Societal costs of Borderline Personality Disorders: a matched‐controlled nationwide study of patients and spouses. (21st September 2019) - Hastrup, L. H.; Jennum, P.; Ibsen, R.; Kjellberg, J.; Simonsen, E.
Abstract : Objective: Information on societal cost of patients with Borderline Personality Disorder (BPD) and spouses is limited. The aim was to investigate factual societal costs before and after initial BPD diagnosis. Method: A register‐based cohort study of 2756 patients with incident BPD (ICD F60.3) with spouses and 11 024 matched controls, during 2002–2016. Results: Total direct healthcare costs and lost productivity costs amounted €40 441 for patients with BPD, which was more than 16 times higher than the matched controls. Somatic and psychiatric health care costs and costs of lost productivity were increased during 5 years before initial diagnosis of BPD. Before and after initial diagnosis, health care costs and lost productivity were increased among spouses of patients with BPD. Conclusion: Patients with BPD differed substantially from the general population with respect to all included costs. The study documented a significant burden on their spouses. Besides the early onset of BPD, which implies that patients are affected before they finish school and enter labor market, the neurocognitive impairment and fundamental symptoms of BPD, e.g. unstable, intense relationships, impulsivity, and lack of stable sense of self together with psychiatric and somatic comorbidity are part of explanation of the excess costs of BPD.